Water shutoff and heat insulation grouting material suitable for high-ground-temperature fractured rock mass and preparation method of water shutoff and heat insulation grouting material

By using cement, biochar, rice husk ash, SiO2 aerogel and other components in the grouting materials, and combining the unique properties of micro-nano bubble water, water blocking and heat-insulating grouting materials suitable for high-temperature environments are prepared, which solves the problem of poor applicability of existing grouting materials in high-temperature environments, and achieves significant heat insulation and water blocking effects.

CN119822744AActive Publication Date: 2025-04-15CHONGQING JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510105777.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The existing grouting materials have poor applicability in high temperature environments and cannot effectively block water reinforcement and insulation, resulting in the problem of heat damage to the environment and economical reduction in tunnel construction.

Method used

The ratio of cement, biochar, rice husk ash, SiO2 aerogel, silicon fume, retarder, stabilizer, water reducing agent and micro-nano bubble water was prepared by stirring and thermal physical and mechanical performance testing.

Benefits of technology

The thermal insulation performance of grouting materials was significantly improved, and the thermal conductivity coefficient was reduced to 0.54W/(m·K), which was 52.63% and 54.24% lower than traditional cement and cement-water glass grouting materials, respectively. At the same time, the water blocking performance and construction efficiency were improved, achieving green environmental protection and resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822744A_ABST
    Figure CN119822744A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of grouting materials, in particular to a water-plugging and heat-insulating grouting material suitable for high-ground-temperature fractured rock mass and a preparation method of the water-plugging and heat-insulating grouting material. Compared with common water commonly used by the grouting material, the introduced micro-nano bubble water is of a closed bubble structure, and the introduced micro-nano bubble water improves the heat insulation performance of the grouting material. The SiO2 aerogel in the grouting material is used as an efficient thermal insulation material and has an extremely low heat conductivity coefficient and relatively high porosity, so that the material can effectively prevent heat transfer in a high-temperature environment. The grouting material is not only suitable for water control engineering of high-ground-temperature fractured rock masses, but also can provide effective heat insulation protection for the rock masses and surrounding underground structures, and the influence of a high-temperature environment on structural safety is reduced. Therefore, the problem that an existing grouting material is poor in applicability in a high-temperature environment is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grouting materials, and in particular to a water-blocking and heat-insulating grouting material suitable for high-temperature fractured rock masses and a preparation method thereof. Background Art

[0002] As transportation construction extends to mountainous areas with complex geology, tunnel engineering is developing in the direction of deep burial, and the tunnel body often needs to pass through more complex geological units. Among them, high ground temperature is one of the typical adverse geological problems in recent years. During the construction of high-temperature tunnels, construction along the tunnel often faces a complex groundwater network. The influx of geothermal water leads to a significant hot and humid environment in the tunnel, and creates greater construction difficulties for tunnel construction. Grouting methods have become the main technical means for water blocking and reinforcement of underground projects due to their high economic benefits and simple construction technology. For high-temperature, water-rich fractured rock tunnels, the grouting process can not only play a role in water blocking and reinforcement, but also can isolate heat sources and reduce the temperature in the tunnel. In the actual construction of high-geotemperature tunnels, advanced curtain grouting can be used to isolate underground hot water and improve the high temperature and high humidity heat damage environment in the tunnel.

[0003] At present, cement or cement-water glass grouting materials are often used in engineering, but they have poor applicability and poor effect in high temperature environment. In fact, the grouting materials made of ordinary cement in high temperature environment have high water separation rate, long setting time, weak anti-scouring ability, reduced strength of cement stone body, difficult to resist the scouring of hot water, and easy to produce the risk of secondary water seepage. In order to meet the effect of grouting and water blocking in tunnel construction, the amount of cement-based grouting is often doubled, which greatly reduces the economy of grouting measures. The gelling time of cement-water glass slurry is shortened in geothermal environment, which reduces the diffusion radius of slurry, making it difficult to form a sufficient curtain grouting layer, and the pipe blocking phenomenon is prone to occur during the grouting process, making it difficult to effectively reinforce the stratum. In addition, the above-mentioned grouting materials prepared with cement or cement-water glass do not have a good thermal insulation effect. The heat in the geothermal water can still be transferred to the tunnel through the curtain grouting ring, which leads to a poor ambient temperature in the tunnel, posing a greater challenge to the formulation of tunnel cooling measures.

[0004] In view of the problems existing in existing tunnel grouting materials, it is necessary to develop a new type of tunnel grouting material and preparation method that is suitable for high geothermal environments and has both water blocking, reinforcement and heat insulation. This can not only ensure the safety requirements of tunnel engineering construction, but also meet the insulation requirements of the tunnel environment throughout the life cycle and save economic investment. It is a topic with important theoretical significance and practical engineering value. Summary of the invention

[0005] The purpose of the present invention is to provide a water-blocking and heat-insulating grouting material and a preparation method suitable for high-temperature fractured rock masses, aiming to solve the problem that existing grouting materials have poor applicability in high-temperature environments.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a water-blocking and heat-insulating grouting material suitable for high-temperature fractured rock mass, comprising the following steps:

[0007] Weigh cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water according to the preset mass fraction;

[0008] Put cement, biochar, rice husk ash, SiO2 aerogel and silica fume into a cement slurry mixer and stir slowly for 120 seconds to obtain a mixture;

[0009] Putting a retarder, a stabilizer and a water reducing agent into the micro-nano bubble water and mixing and stirring to obtain a micro-nano bubble aqueous solution;

[0010] The micro-nano bubble aqueous solution and the mixture are added into a stirring pot and stirred slowly for 60 seconds and quickly for 60 seconds to obtain a mixed grouting slurry material;

[0011] The mixed grouting slurry material was placed in 60°C hot water in a magnetic stirring water bath and then heated at a constant temperature for thermal physical and mechanical properties testing;

[0012] The tested mixed grouting slurry material is cast into a mold and then placed in a curing box for curing to obtain a high-temperature environment water-blocking grouting material.

[0013] Among them, in “weighing cement, biochar, rice husk ash, SiO2 aerogel, silica ash, retarder, stabilizer, water reducer and micro-nano bubble water according to preset mass fractions”, the mass fraction of the cement content is 30-70%; the mass fraction of the biochar content is 1-5%; the mass fraction of the rice husk content is 3-8%; the mass fraction of the SiO2 aerogel content is 15-30%; the mass fraction of the silica ash content is 2-6%; the mass fraction of the retarder content is 0.5-5%; the mass fraction of the stabilizer content is 0.2-1.5%; the mass fraction of the water reducer is 0.2-1.5%; and the mass fraction of the micro-nano bubble water content is 45%.

[0014] Among them, in "weighing cement, biochar, rice husk ash, SiO2 aerogel, silica ash, retarder, stabilizer, water reducer and micro-nano bubble water according to preset mass fractions", the cement is ordinary Portland cement with a strength grade of not less than 42.5MPa; the biochar is made by pyrolysis of wheat straw in a partially oxygen-deficient environment; the rice husk ash is prepared by low-temperature combustion of rice husks; the SiO2 aerogel is nano aerogel powder; the silica ash is fine silica ash; the retarder is boric acid or sodium fluorosilicate, calcium lignin sulfonate; the stabilizer is any one of cellulose ether, polyvinyl alcohol or water-soluble starch; the water reducer is naphthalene-based, polycarboxylic acid-based, melamine-based, or lignin-based water reducer; and the micro-nano bubble water is a non-chemical liquid medium for nano-scale bubbles.

[0015] Among them, in “weighing cement, biochar, rice husk ash, SiO2 aerogel, silica ash, retarder, stabilizer, water reducer and micro-nano bubble water according to preset mass fractions”, the particle size of the biochar is ≤100 mesh; the thermal conductivity of the SiO2 aerogel is 0.013-0.020 W / (m·K), the particle size is ≤3 mm, the pore size is 20-40 nm, and the porosity is >90%; the average particle size of the silica ash is 0.1-0.3 μm, and the density is 2.33 g / cm 3 , with a specific surface area of ​​20.5m 2 ·kg; the bubble diameter of the micro-nano bubble water is 10-200nm, and the bubble concentration is 10 8 -10 9 Pieces / ml.

[0016] Among them, in “putting cement, biochar, rice husk ash, SiO2 aerogel and silica ash into a cement slurry mixer and slowly stirring for 120 seconds to obtain a mixture”, the following steps are included:

[0017] Place cement, biochar, rice husk ash, SiO2 aerogel, and silica ash into a mixer in sequence;

[0018] Set the blender to slow blending mode and blend for 120 seconds;

[0019] When blending is complete, turn off the blender and use a spatula to remove the mixture from the blender and place in a clean container for later use.

[0020] Among them, the step of “putting a retarder, a stabilizer and a water reducing agent into micro-nano bubble water for mixing and stirring to obtain a micro-nano bubble aqueous solution” includes the following steps:

[0021] Add the weighed retarder, stabilizer and water reducer into the container containing micro-nano bubble water in sequence;

[0022] After setting the stirring speed of the electric stirrer, mix and stir the materials in the container;

[0023] Take out the micro-nano bubble aqueous solution in the container for later use.

[0024] Among them, in “adding the micro-nano bubble aqueous solution and the mixture into a stirring pot and stirring slowly for 60 seconds and rapidly for 60 seconds to obtain a mixed grouting slurry material”, the following steps are included:

[0025] Add the prepared mixture and the micro-nano bubble aqueous solution into a stirring pot respectively;

[0026] Set the mixing pot to slow mixing mode and mix slowly for 60 seconds;

[0027] Set the mixing pot to the fast mixing mode and mix quickly for 60 seconds;

[0028] After the stirring is completed, the stirring pot is turned off, and the mixed grouting slurry material is taken out from the stirring pot by a scraper and placed in a container for later use.

[0029] Among them, in “casting the tested mixed grouting slurry material into a mold and then placing it in a curing box for curing to obtain a high-temperature environment water plugging grouting material”, the following steps are included:

[0030] The mixed grouting slurry material after the test was poured into a 40×40×160 mm mold, and the mold was removed 24 hours after molding to obtain a semi-finished product;

[0031] The semi-finished product is placed in a cement mortar rapid curing box at 60°C for standard 28 days of curing to obtain a high temperature environment water plugging grouting material.

[0032] In the second aspect, a water-blocking and heat-insulating grouting material adapted to high geothermal fractured rock mass adopts the preparation method of the water-blocking and heat-insulating grouting material adapted to high geothermal fractured rock mass described in the first aspect, including cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water.

[0033] The preparation method of the water-blocking and heat-insulating grouting material suitable for high-temperature fractured rock mass of the present invention comprises the following steps: weighing cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water according to preset mass fractions; putting cement, biochar, rice husk ash, SiO2 aerogel and silica fume into a cement slurry mixer and stirring slowly for 120 seconds to obtain a mixture; putting the retarder, stabilizer and water reducer into the micro-nano bubble water for mixing and stirring to obtain a micro-nano bubble aqueous solution; adding the micro-nano bubble aqueous solution and the mixture into a stirring pot for 60 seconds slow stirring and 60 seconds fast stirring to obtain a mixed grouting slurry material; placing the mixed grouting slurry material in 60°C hot water and heating it at constant temperature by a magnetic stirring water bath pot to perform a thermal physical and mechanical property test; casting the tested mixed grouting slurry material into a mold and placing it in a curing box for curing to obtain a high-temperature environment water-blocking grouting material. The present invention prepares a grouting material with both water blocking and heat insulation effects. Compared with the common water commonly used in grouting materials, the introduction of micro-nano bubble water is a closed bubble structure, and its introduction improves the thermal insulation performance of the grouting material. As a highly efficient thermal insulation material, the SiO2 aerogel in the grouting material has an extremely low thermal conductivity and a high porosity, which enables the material to effectively prevent the transfer of heat in a high temperature environment. The grouting material of the present invention is not only suitable for water control projects in high-temperature fractured rock masses, but also can provide effective thermal insulation protection for the rock mass and the surrounding underground structures, reduce the impact of the high temperature environment on the structural safety, and thus solve the problem of poor applicability of existing grouting materials in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 The present invention provides a flow chart of a method for preparing a water-blocking and heat-insulating grouting material suitable for high-temperature fractured rock masses.

[0036] Figure 2 The flow chart is that cement, biochar, rice husk ash, SiO2 aerogel and silica fume are put into a cement slurry mixer and slowly stirred for 120 seconds to obtain a mixture.

[0037] Figure 3 The present invention is a flow chart of putting a retarder, a stabilizer and a water reducing agent into micro-nano bubble water for mixing and stirring to obtain a micro-nano bubble aqueous solution.

[0038] Figure 4The present invention is a flow chart of adding the micro-nano bubble aqueous solution and the mixture into a stirring pot, stirring slowly for 60 seconds and stirring quickly for 60 seconds to obtain a mixed grouting slurry material.

[0039] Figure 5 The flow chart is that the mixed grouting slurry material after the test is cast into a mold and then placed in a curing box for curing to obtain the water-blocking grouting material for a high-temperature environment. DETAILED DESCRIPTION

[0040] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0041] See also Figures 1 to 5 In a first aspect, the present invention provides a method for preparing a water-blocking and heat-insulating grouting material suitable for high-temperature fractured rock mass, comprising the following steps:

[0042] S1 weighs cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water according to the preset mass fraction;

[0043] The mass fraction of the cement content is 30-70%; the mass fraction of the biochar content is 1-5%; the mass fraction of the rice husk content is 3-8%; the mass fraction of the SiO2 aerogel content is 15-30%; the mass fraction of the silica fume content is 2-6%; the mass fraction of the retarder content is 0.5-5%; the mass fraction of the stabilizer content is 0.2-1.5%; the mass fraction of the water reducer content is 0.2-1.5%; and the mass fraction of the micro-nano bubble water content is 45%.

[0044] The cement is ordinary Portland cement with a strength grade of not less than 42.5MPa; the biochar is made by pyrolysis of wheat straw in a partially oxygen-deficient environment; the rice husk ash is prepared by low-temperature combustion of rice husk; the SiO2 aerogel is nano aerogel powder; the silica ash is fine silica ash; the retarder is boric acid or sodium fluorosilicate, calcium lignin sulfonate; the stabilizer is any one of cellulose ether, polyvinyl alcohol or water-soluble starch; the water reducer is a naphthalene-based, polycarboxylic acid-based, melamine-based, or lignin-based water reducer; and the micro-nano bubble water is a non-chemical liquid medium for nano-scale bubbles.

[0045] The particle size of the biochar is ≤100 mesh; the thermal conductivity of the SiO2 aerogel is 0.013-0.020 W / (m·K), the particle size is ≤3 mm, the pore size is 20-40 nm, and the porosity is >90%; the average particle size of the silica ash is 0.1-0.3 μm, and the density is 2.33 g / cm 3 , with a specific surface area of ​​20.5m 2 ·kg; the bubble diameter of the micro-nano bubble water is 10-200nm, and the bubble concentration is 10 8 -10 9 Pieces / ml.

[0046] Specifically, an electronic scale is used to weigh cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water one by one according to the preset mass fraction to ensure accurate weighing. The weighed raw materials are placed in clean containers and labeled to prevent confusion.

[0047] S2: putting cement, biochar, rice husk ash, SiO2 aerogel and silica fume into a cement slurry mixer and slowly stirring for 120 seconds to obtain a mixture;

[0048] S21 put cement, biochar, rice husk ash, SiO2 aerogel and silica ash into a mixer in sequence;

[0049] Specifically, open the lid of the cement slurry mixer, and add cement, biochar, rice husk ash, SiO2 aerogel and silica ash into the mixer in order.

[0050] S22 sets the mixer to slow stirring mode and stirs for 120 seconds;

[0051] Specifically, the mixer is set to slow stirring mode and the stirring speed is controlled within an appropriate range to avoid splashing of raw materials and overloading of the mixer. The stirring time is set to 120 seconds to ensure that the raw materials are fully mixed. During the stirring process, the operating status of the mixer and the uniformity of the mixture are observed.

[0052] S23 After the mixing is completed, turn off the mixer and use a scraper to remove the mixture from the mixer and place it in a clean container for later use.

[0053] Specifically, after blending, turn off the blender and wait for it to completely stop running, then open the lid. Use a scraper or spatula to remove the mixture from the blender and place it in a clean container for later use.

[0054] S3: putting a retarder, a stabilizer and a water reducing agent into the micro-nano bubble water for mixing and stirring to obtain a micro-nano bubble aqueous solution;

[0055] S31 adding weighed retarder, stabilizer and water reducer into a container containing micro-nano bubble water in sequence;

[0056] Specifically, the weighed retarder, stabilizer and water reducer are added into a container filled with micro-nano bubble water in sequence.

[0057] S32 sets the stirring speed of the electric stirrer to mix and stir the materials in the container;

[0058] Specifically, an electric stirrer or a magnetic stirrer is used to mix and stir the materials in the container. The stirring speed should be moderate to avoid generating too many bubbles or destroying the structure of the micro-nano bubbles. The stirring time is determined according to the specific situation until all components are completely dissolved and evenly distributed in the micro-nano bubble water.

[0059] S33: taking out the micro-nano bubble aqueous solution in the container for later use.

[0060] Specifically, after the stirring is finished, the stirrer is turned off and waits for it to completely stop running, and then the micro-nano bubble aqueous solution in the container is taken out for use.

[0061] S4: adding the micro-nano bubble aqueous solution and the mixture into a stirring pot and stirring slowly for 60 seconds and rapidly for 60 seconds to obtain a mixed grouting slurry material;

[0062] S41, adding the prepared mixture and the micro-nano bubble aqueous solution into a stirring pot respectively;

[0063] Specifically, the prepared mixture and the micro-nano bubble aqueous solution are added into a stirring pot respectively.

[0064] S42 sets the stirring pot to the slow stirring mode for 60 seconds of slow stirring;

[0065] Specifically, the stirring pot is set to a slow stirring mode for 60 seconds. The stirring speed should be moderate to ensure that the raw materials are fully mixed.

[0066] S43 sets the stirring pot to the rapid stirring mode for 60 seconds of rapid stirring;

[0067] Specifically, the stirring pot is then set to a rapid stirring mode for 60 seconds. Rapid stirring helps to improve the uniformity and fluidity of the grouting material, providing favorable conditions for subsequent construction and curing.

[0068] S44 After the stirring is completed, the stirring pot is closed and the mixed grouting slurry material is taken out from the stirring pot by a scraper and placed in a container for later use.

[0069] Specifically, after the stirring is completed, the stirring pot is turned off and waited for it to completely stop running, and then the mixed grouting slurry material is taken out from the stirring pot by a scraper and placed in a container for standby use.

[0070] S5 puts the mixed grouting slurry material in 60℃ hot water in a magnetic stirring water bath and then conducts a thermal physical and mechanical property test after constant temperature heating;

[0071] Specifically, the temperature of the magnetic stirring water bath is set to 60°C, and the mixed grouting slurry material is placed in the water bath for constant temperature water heating. During the heating process, a magnetic stirring bar is used for stirring to ensure that the slurry is evenly heated. During the heating process, the mixed grouting slurry material is regularly tested for thermal physical and mechanical properties. The test items include but are not limited to compressive strength, impermeability, thermal insulation, etc. The test data is recorded for subsequent analysis and evaluation of the performance of the grouting material.

[0072] S6 casts the tested mixed grouting slurry material into a mold and places it in a curing box for curing to obtain a high-temperature environment water-blocking grouting material.

[0073] S61: Pour the tested mixed grouting slurry material into a 40×40×160 mm mold, remove the mold 24 hours after molding, and obtain a semi-finished product;

[0074] Specifically, a suitable mold (such as a 40×40×160 mm mold) is selected and the mixed grouting slurry material after the test is poured into the mold. A scraper or shovel is used to flatten the grouting material in the mold to ensure that it is evenly distributed. After the grouting material is initially solidified (such as after 24 hours), the mold is removed to obtain a semi-finished product.

[0075] S62 places the semi-finished product in a 60°C cement mortar rapid curing box for standard 28-day curing to obtain a high-temperature environment water-blocking grouting material.

[0076] Specifically, the semi-finished product after demolding is placed in a cement mortar rapid curing box at 60°C for a standard 28-day curing treatment. During the curing process, the hardening condition and performance changes of the grouting material are regularly checked to ensure that it meets the predetermined performance requirements.

[0077] Embodiment 1:

[0078] The city tap water is prepared into micro-nano bubble water by using a micro-nano bubble generator, and the water is left to stand for 1 hour to eliminate the bubbles with poor stability before being used;

[0079] Mass fraction of each component: P·O42.5 ordinary Portland cement 85%, biochar 5%, rice husk ash 5%, silica fume 2%, retarder 1.5%, stabilizer 0.5%, high-efficiency water reducer 1%, micro-nano bubble water 45%;

[0080] Among them, the mass ratio of boric acid or sodium fluorosilicate to calcium lignin sulfonate in the retarder is 1:5; the mass ratio of naphthalene series, polycarboxylic acid series, melamine series and lignin series in the water reducer is 1.1:3.7:1.5:1.9.

[0081] According to the mass fraction, the weighed ordinary silicate cement, biochar, rice husk ash, SiO2 aerogel and silica ash were put into the cement slurry mixer and slowly stirred for 120s; then, according to the mass fraction, the weighed retarder, stabilizer and high-efficiency water reducer were put into the corresponding weighed micro-nano bubble water for full stirring, and then the micro-nano bubble water solution was poured into the stirring pot for slow stirring for 60s and rapid stirring for 60s to obtain the mixed grouting slurry material; then, the prepared slurry was heated at a constant temperature in 60°C hot water in a magnetic stirring water bath, and then the thermal physical and mechanical properties were tested; finally, the cement-based grouting material slurry was poured into a 40×40×160mm mold, and the mold was removed 24h after molding, and placed in a cement mortar rapid curing box at a temperature of 60°C for standard 28d curing, so as to obtain the high temperature environment water plugging grouting material

[0082] Material testing indicators are as follows:

[0083] Under a high temperature environment of 60℃, the initial setting time of cement mortar is 214min, the final setting time is 253min, the water separation rate is 2.18%, the 3d, 7d, and 21d compressive strengths are 8.7MPa, 9.8MPa, and 1.1MPa respectively, and the thermal conductivity is 1.02W / (m·K).

[0084] Embodiment 2:

[0085] The city tap water is prepared into micro-nano bubble water by using a micro-nano bubble generator, and the water is left to stand for 1 hour to eliminate the bubbles with poor stability before being used;

[0086] The mass fraction of each component is: P·O42.5 ordinary Portland cement 65%, biochar 4%, rice husk ash 6%, SiO2 aerogel 17%, silica fume 3%, retarder 3%, stabilizer 0.8%, high-efficiency water reducer 1.2%, micro-nano bubble water 45%;

[0087] Among them, the mass ratio of boric acid or sodium fluorosilicate to calcium lignin sulfonate in the retarder is 1:5; the mass ratio of naphthalene series, polycarboxylic acid series, melamine series and lignin series in the water reducer is 1.5:3.1:1.2:2.2.

[0088] According to the mass fraction, the weighed ordinary silicate cement, biochar, rice husk ash, SiO2 aerogel and silica ash were put into the cement slurry mixer and slowly stirred for 120s; then, according to the mass fraction, the weighed retarder, stabilizer and high-efficiency water reducer were put into the corresponding weighed micro-nano bubble water for full stirring, and then the micro-nano bubble water solution was poured into the stirring pot for slow stirring for 60s and rapid stirring for 60s to obtain the mixed grouting slurry material; then, the prepared slurry was heated at a constant temperature in 60°C hot water in a magnetic stirring water bath, and then the thermal physical and mechanical properties were tested; finally, the cement-based grouting material slurry was poured into a 40×40×160mm mold, and the mold was removed 24h after molding, and placed in a cement mortar rapid curing box at a temperature of 60°C for standard 28d curing, so as to obtain the high temperature environment water plugging grouting material

[0089] Material testing indicators are as follows:

[0090] Under a high temperature environment of 60℃, the initial setting time of cement mortar is 141min, the final setting time is 168min, the water separation rate is 1.58%, the 3d, 7d, and 21d compressive strengths are 6.4MPa, 8.5MPa, and 9.1MPa respectively, and the thermal conductivity is 0.67W / (m·K).

[0091] Embodiment 3:

[0092] The city tap water is prepared into micro-nano bubble water by using a micro-nano bubble generator, and the water is left to stand for 1 hour to eliminate the bubbles with poor stability before being used;

[0093] The mass fraction of each component is: P·O42.5 ordinary Portland cement 55%, biochar 5%, rice husk ash 7%, SiO2 aerogel 25%, silica fume 3.5%, retarder 2.5%, stabilizer 0.8%, high-efficiency water reducer 1.2%, micro-nano bubble water 45%;

[0094] Among them, the mass ratio of boric acid or sodium fluorosilicate to calcium lignin sulfonate in the retarder is 1:5; the mass ratio of naphthalene series, polycarboxylic acid series, melamine series and lignin series in the water reducer is 1.3:2.9:1.1:1.8.

[0095] According to the mass fraction, the weighed ordinary silicate cement, biochar, rice husk ash, SiO2 aerogel and silica ash were put into the cement slurry mixer and slowly stirred for 120s; then, according to the mass fraction, the weighed retarder, stabilizer and high-efficiency water reducer were put into the corresponding weighed micro-nano bubble water for full stirring, and then the micro-nano bubble water solution was poured into the stirring pot for slow stirring for 60s and rapid stirring for 60s to obtain the mixed grouting slurry material; then, the prepared slurry was heated at a constant temperature in 60°C hot water in a magnetic stirring water bath, and then the thermal physical and mechanical properties were tested; finally, the cement-based grouting material slurry was poured into a 40×40×160mm mold, and the mold was removed 24h after molding, and placed in a cement mortar rapid curing box at a temperature of 60°C for standard 28d curing, so as to obtain the high temperature environment water plugging grouting material

[0096] Material testing indicators are as follows:

[0097] Under a high temperature environment of 60℃, the initial setting time of cement mortar is 134min, the final setting time is 153min, the water separation rate is 1.44%, the compressive strengths at 3d, 7d and 21d are 5.4MPa, 6.8MPa and 7.6MPa respectively, and the thermal conductivity is 0.62W / (m·K).

[0098] Embodiment 4:

[0099] The city tap water is prepared into micro-nano bubble water by using a micro-nano bubble generator, and the water is left to stand for 1 hour to eliminate the bubbles with poor stability before being used;

[0100] Mass fraction of each component: P·O42.5 ordinary Portland cement 40%, biochar 7%, rice husk ash 8%, SiO2 aerogel 35%, silica fume 4%, retarder 3.2%, stabilizer 1.2%, high-efficiency water reducer 1.6%, micro-nano bubble water 45%;

[0101] Among them, the mass ratio of boric acid or sodium fluorosilicate to calcium lignin sulfonate in the retarder is 1:5; the mass ratio of naphthalene series, polycarboxylic acid series, melamine series and lignin series in the water reducer is 1.2:2.5:1.8:2.5.

[0102] According to the mass fraction, the weighed ordinary silicate cement, biochar, rice husk ash, SiO2 aerogel and silica ash were put into the cement slurry mixer and slowly stirred for 120s; then, according to the mass fraction, the weighed retarder, stabilizer and high-efficiency water reducer were put into the corresponding weighed micro-nano bubble water for full stirring, and then the micro-nano bubble water solution was poured into the stirring pot for slow stirring for 60s and rapid stirring for 60s to obtain the mixed grouting slurry material; then, the prepared slurry was heated at a constant temperature in 60°C hot water in a magnetic stirring water bath, and then the thermal physical and mechanical properties were tested; finally, the cement-based grouting material slurry was poured into a 40×40×160mm mold, and the mold was removed 24h after molding, and placed in a cement mortar rapid curing box at a temperature of 60°C for standard 28d curing, so as to obtain the high temperature environment water plugging grouting material

[0103] Material testing indicators are as follows:

[0104] Under a high temperature environment of 60℃, the initial setting time of cement mortar is 145min, the final setting time is 176min, the water separation rate is 1.24%, the compressive strengths at 3d, 7d and 21d are 4.2MPa, 5.3MPa and 6.2MPa respectively, and the thermal conductivity is 0.54W / (m·K).

[0105] It can be seen from the above four implementation plans that the high geothermal fractured rock water blocking and heat insulation grouting material prepared by the present invention can reach a minimum thermal conductivity of 0.54W / (m·K) on the basis of satisfying the requirements of compressive strength. Compared with the thermal conductivity of the existing ordinary cement grouting material of 1.18W / (m·K) and the thermal conductivity of the cement-water glass grouting material of 1.14W / (m·K), the invented grouting insulation material is reduced by 52.63% and 54.24% respectively, which can effectively block the conduction of heat flow. The optimal material ratio is recommended to be cement: biochar: rice husk ash: SiO2 aerogel: nano bubble water: retarder: stabilizer: water reducer = 1.00: 0.18: 0.20: 0.88: 0.10: 0.08: 0.04: 0.04. Appropriate addition of biochar and rice husk ash to the material can not only reduce the thermal conductivity of the slurry to a certain extent, but also develop green, environmentally friendly and energy-saving geopolymer grouting materials; the addition of SiO2 aerogel and micro-nano bubble water made by a micro-nano bubble generator can form a closed porous structure in the cement slurry, greatly improving the thermal insulation performance of the grouting material, and has great application value in high geothermal fractured rock environments.

[0106] In the second aspect, a water-blocking and heat-insulating grouting material adapted to high geothermal fractured rock mass adopts the preparation method of the water-blocking and heat-insulating grouting material adapted to high geothermal fractured rock mass described in the first aspect, including cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water.

[0107] Beneficial effects:

[0108] 1. Significantly improve thermal insulation performance: By rationally mixing raw materials such as cement, biochar, rice husk ash, SiO2 aerogel, and combining the unique properties of micro-nano bubble water, the thermal conductivity of the prepared grouting material is significantly reduced, as low as 0.54W / (m·K), which is 52.63% and 54.24% lower than that of traditional cement grouting materials and cement-water glass grouting materials, respectively. This feature enables the grouting material to effectively block the conduction of heat flow in high geothermal fractured rock environments, providing a strong guarantee for the stability and safety of underground projects.

[0109] 2. The water blocking performance and effect of grouting materials in high geothermal environments are improved, the predetermined grouting range can be achieved, the water blocking effect is improved, etc.

[0110] 3. Green environmental protection and resource recycling: The reuse of biochar and rice husk ash as agricultural waste not only reduces environmental pollution, but also realizes the recycling of resources. At the same time, the addition of high-performance materials such as SiO2 aerogel also improves the overall performance of grouting materials, making them more environmentally friendly and efficient.

[0111] 4. Optimize material performance and construction efficiency: Through precise component design and preparation process, grouting materials show excellent performance in strength, thermal insulation and stability.

[0112] 5. Broad application prospects: The grouting material prepared by the present invention is not only suitable for water control projects and thermal insulation protection of high-temperature fractured rock masses, but also can be used for the control of geological disasters, the development of underground resources, and the waterproofing, plugging and thermal insulation protection of underground projects such as underground pipelines and tunnels. Its broad application prospects and huge market potential provide strong support for the advancement and sustainable development of underground engineering technology.

[0113] The above disclosure is only a preferred embodiment of the water-blocking and heat-insulating grouting material and preparation method suitable for high-temperature fractured rock masses of the present invention. Of course, this cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass, characterized by: The following steps are involved: Weigh cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water according to the preset mass fraction; Put cement, biochar, rice husk ash, SiO2 aerogel and silica fume into a cement slurry mixer and stir slowly for 120 seconds to obtain a mixture; Putting a retarder, a stabilizer and a water reducing agent into the micro-nano bubble water and mixing and stirring to obtain a micro-nano bubble aqueous solution; The micro-nano bubble aqueous solution and the mixture are added into a stirring pot and stirred slowly for 60 seconds and quickly for 60 seconds to obtain a mixed grouting slurry material; The mixed grouting slurry material was placed in 60°C hot water in a magnetic stirring water bath and then heated at a constant temperature for thermal physical and mechanical properties testing; The tested mixed grouting slurry material is cast into a mold and then placed in a curing box for curing to obtain a high-temperature environment water-blocking grouting material.

2. The method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass according to claim 1, characterized in that: In "weighing cement, biochar, rice husk ash, SiO2 aerogel, silica ash, retarder, stabilizer, water reducer and micro-nano bubble water according to preset mass fractions", the mass fraction of the cement content is 30-70%; the mass fraction of the biochar content is 1-5%; the mass fraction of the rice husk content is 3-8%; the mass fraction of the SiO2 aerogel content is 15-30%; the mass fraction of the silica ash content is 2-6%; the mass fraction of the retarder content is 0.5-5%; the mass fraction of the stabilizer content is 0.2-1.5%; the mass fraction of the water reducer is 0.2-1.5%; and the mass fraction of the micro-nano bubble water content is 45%.

3. The method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass according to claim 1, characterized in that: In "weighing cement, biochar, rice husk ash, SiO2 aerogel, silica ash, retarder, stabilizer, water reducer and micro-nano bubble water according to preset mass fractions", the cement is ordinary Portland cement with a strength grade of not less than 42.5 MPa; the biochar is made by pyrolysis of wheat straw in a partially anoxic environment; the rice husk ash is prepared by low-temperature combustion of rice husks; the SiO2 aerogel is nano aerogel powder; the silica ash is fine silica ash; the retarder is boric acid or sodium fluorosilicate, calcium lignin sulfonate; the stabilizer is any one of cellulose ether, polyvinyl alcohol or water-soluble starch; the water reducer is a naphthalene-based, polycarboxylic acid-based, melamine-based or lignin-based water reducer; and the micro-nano bubble water is a non-chemical liquid medium for nano-sized bubbles.

4. The method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass according to claim 1, characterized in that: In "weighing cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water according to preset mass fractions", the particle size of the biochar is ≤100 mesh; the thermal conductivity of the SiO2 aerogel is 0.013-0.020 W / (m·K), the particle size is ≤3 mm, the pore size is 20-40 nm, and the porosity is >90%; the average particle size of the silica fume is 0.1-0.3 μm, and the density is 2.33 g / cm 3 , with a specific surface area of ​​20.5m 2 ·kg; the bubble diameter of the micro-nano bubble water is 10-200nm, and the bubble concentration is 10 8 -10 9 Pieces / ml.

5. The method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass according to claim 1, characterized in that: In "putting cement, biochar, rice husk ash, SiO2 aerogel and silica ash into a cement slurry mixer and slowly stirring for 120 seconds to obtain a mixture", the following steps are included: Place cement, biochar, rice husk ash, SiO2 aerogel, and silica ash into a mixer in sequence; Set the blender to slow blending mode and blend for 120 seconds; When blending is complete, turn off the blender and use a spatula to remove the mixture from the blender and place in a clean container for later use.

6. The method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass according to claim 1, characterized in that: The step of "putting a retarder, a stabilizer and a water reducing agent into micro-nano bubble water for mixing and stirring to obtain a micro-nano bubble aqueous solution" includes the following steps: Add the weighed retarder, stabilizer and water reducer into the container containing micro-nano bubble water in sequence; After setting the stirring speed of the electric stirrer, mix and stir the materials in the container; Take out the micro-nano bubble aqueous solution in the container for later use.

7. The method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass according to claim 1, characterized in that: In “adding the micro-nano bubble aqueous solution and the mixture into a stirring pot and stirring slowly for 60 seconds and rapidly for 60 seconds to obtain a mixed grouting slurry material”, the following steps are included: Add the prepared mixture and the micro-nano bubble aqueous solution into a stirring pot respectively; Set the mixing pot to slow mixing mode and mix slowly for 60 seconds; Set the mixing pot to the fast mixing mode and mix quickly for 60 seconds; After the stirring is completed, the stirring pot is turned off, and the mixed grouting slurry material is taken out from the stirring pot by a scraper and placed in a container for later use.

8. The method for preparing water-blocking and heat-insulating grouting materials suitable for high-temperature fractured rock mass according to claim 1, characterized in that: In "casting the tested mixed grouting slurry material into a mold and then placing it in a curing box for curing to obtain a high-temperature environment water plugging grouting material", the following steps are included: The mixed grouting slurry material after the test was poured into a 40×40×160 mm mold, and the mold was removed 24 hours after molding to obtain a semi-finished product; The semi-finished product is placed in a cement mortar rapid curing box at 60°C for standard 28 days of curing to obtain a high temperature environment water plugging grouting material.

9. A water-blocking and heat-insulating grouting material adapted to high-temperature fractured rock mass, comprising: Including cement, biochar, rice husk ash, SiO2 aerogel, silica fume, retarder, stabilizer, water reducer and micro-nano bubble water.

Citation Information

Patent Citations

  • Micro-nano bubble water tailing concrete and preparation method thereof

    CN114605097A

  • Micro-nano bubble slurry material

    CN117466615A

  • Production method of foundation injection material, and foundation improving method

    JP2014159503A

  • Method for producing hardened product

    WO2024204119A1